The mediating effect of brand identity on brand knowledge and the operational development of universities - Chin-Tsu Chen (South African Journal of Business Management, 2019)
Background: In the research field of Taiwanese university education and from the viewpoint of university institutions, brand knowledge plays a crucial role in their development.Objectives: The main purpose of this study was to explore how the reputation and images of universities affect their competitiveness development from the perspective of brand knowledge.Method: The study collects information from 600 questionnaire surveys Issued to students and graduates of universities in Taiwan, receiving 468 valid questionnaires.Results: The results analysed by structural equation modelling show that: (1) brand awareness has a significant positive influence on brand identity; (2) brand image has a significant positive influence on brand identity; (3) brand identity has a significant positive influence on satisfied experience sharing; (4) brand identity has a significant positive influence on recommendation to others; and (5) brand awareness and brand image both exert an influence on satisfied experience sharing and recommendation to others through the mediating effect of brand identity.Conclusion: The brand identity model developed in the study for evaluating the effects of higher education institutions helps to explain and predict the influence of brand knowledge on the word-of-mouth communication behaviour of university students. These results should help effectively shape the individual association of schools and provide a reference for the marketing strategy development of higher education institutions.
Keywords: 650